PERANCANGAN SISTEM INFORMASI KOPERASI POKMAS KELUARGA BESAR STT CIPASUNG TASIKMALAYA - Zamakhsyari Sidiq, Ahmad; Sabar Jamil, Mohammad; Hidayatulloh, Asep (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
KKB STT Cipasung, is one of the cooperatives in Tasikmalaya Regency. So far, the cooperative has experienced several problems, including lost savings books, differences in the data on the version of the savings book held by members and savings data in the cooperative, and the difficulty of making financial reports. Based on this, a website-based cooperative information system was designed using the SDLC Waterfall method. The results of designing a cooperative information system can be accessed by members anytime and anywhere as long as they have a cellphone or computer with internet access. The savings data seen by members is always the same as the data held by the management. Financial reports can be automatically created after all transactions are input and can be checked in real time.